Insect Communities Associated with Siam Weed: Evaluation after Three Decades of Cecidochares connexa Release as Biocontrol Agent - Damayanti Buchori; Akhmad Rizali; Luna Lukvitasari; Hermanu Triwidodo (Diversity, 2020)
Chromolaena odorata is well known as an invasive weed, and its existence in agricultural habitats causes an undesirable effect on crop plants. The invasion of C. odorata alters local biodiversity and shapes the new trophic interaction with local herbivores and other insects. This research was conducted to study the insect communities associated with C. odorata and evaluate the success of the release of Cecidochares connexa, the natural enemy of C. odorata. Field research was conducted in two different geographical regions in Bogor Regency (Java) and South Lampung Regency (Sumatera), Indonesia. In each region, we selected five villages that have two land-use types (oil palm plantations and open area) and contain a high population of C. odorata. Observation of insects and natural enemies of C. odorata was conducted in each land-use type using two methods: suction sampling and gall collection, which were performed in 30 plants as sampling units. In total, we found 255 species of insects associated with C. odorata. The difference of region affected the abundance of insects but not their species richness. The species composition of insects showed difference between regions as well as between land-use types. There was a positive correlation between elevation and species richness of insects. In addition, the population of C. connexa (gall numbers) was significantly affected by regions and was found to be higher in Bogor and Lampung. The same pattern also was shown for its parasitoids (based on parasitized galls). We found a negative relationship between the number as well as parasitize galls and elevation. In conclusion, the presence of C. odorata, as well as its natural enemies, shape the new trophic interaction with local insects, and as consequence, its introduced natural enemies may not be effective to control the population of C. odorata.